Environmental life cycle considerations for design-related decision making in minerals processing - Stewart, Mary (Department of Chemical Engineering, 2016)
The objective of this work is to inform environmental decision making in design for the environment in minerals processing. To this end an integrated decision hierarchy has been developed. This decision hierarchy incorporates technical, environmental and social considerations in the design process. Life Cycle Assessment (LCA) has been chosen as the metric whereby environmental considerations will be included in the decision making process. LCA information is augmented by information from the Environmental Impact Assessment (EIA) process in detailed design. There are four themes in this thesis; Minerals Processing, Process Design, LCA and Decision Making. Considerations specific to process design in the minerals industry are highlighted. The use ofLCA as a tool to assess the environmental performance of the minerals industry is discussed. LCA is then used to inform the decisions taken during process design.